Web-based STMIK AKBA Student Attendance Information System by Making QR Codes an Auxiliary Medium - Akbar Iskandar; Robbi Rahim; Harfawan Matturungan; Mansyur (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
The attendance or attendance system is a recording or provision of information on a person's presence which indicates that the person has provided information about his presence and absence, then it is stated in the form of an attendance report. Along with the development of technology, an attendance recording has also developed, where we used to use paper attendance to fingerprint attendance. In educational institutions such as campuses, attendance has an important role in the process of developing a student. Until now, there are still many campuses that still use conventional attendance to record the presence of students in class, which allows for human error or fraud from both lecturers and students. Therefore, a solution is possible to suppress errors that may occur, namely by creating a website-based attendance or attendance system where the QR Code is used as an auxiliary medium in recording the presence or absence of a student at the STMIK AKBA Makassar Campus.